PENINGKATAN PEMAHAMAN KOSAKATA PADA ANAK MELALUI PERMAINAN ABACA FLASHCARD SERI 1 RA AL MA’RUF PURWOREJO BONANG DEMAK - Ismah Jauharin Farda; Fu’ad Arif Noor (STPI Bina Insan Mulia Yogyakarta, 2024)
The purpose of the thesis research entitled improving children’s vocabulary understanding through the Abaca Flashcard Series 1 game at RA Al Ma’ruf Purworejo Bonang Demak is to find out the implementation of the Abaca Flashcard Series 1 game at RA Al Ma’ruf Purworejo Bonang Demak. And to find out the improvement of children’s vocabulary understanding through the Abaca Flashcard series 1 game at RA Al Ma’ruf Purworejo Bonang Demak. The research method used in this study is the Classroom Action Research Method using the Kemmis and McTaggart model research which uses a self-reflection spiral system where each cycle includes four components or stages, namely planning, action, observing, and reflecting. The cycle consists of pre-cycle, cycle l, cycle II. The assesment tool uses an observation sheet instrument in the form of a cheklist. Data collection techniques are carried out using observation and documentation techniques. The subjects of the study were Group B students at RA Al Ma’ruf Purworejo Bonang Demak totaling 15 students with 9 male students and 6 female students. The results of the study showed an increase in vocabulary understanding in froup B children with the Abaca flashcard series 1 game at RA Al Ma’ruf Purworejo Bonang Demak. This is based on an increase in childrens vocabulary understanding from each cycle. It can be seen from the percentage value in the pre-cycle reashing 13,3% then in cycle I the persentage value reached 66,6%. After the implementation of cycle II the persentage value reashed 93,3%. This means that there has been an increase in children’s vocabulary understanding from the pre-cycle to the second cycle of.